(untitled) (Bangladesh Journal of Plant Taxonomy, 2015)
This study examines the exomorphic achene characteristics of 23 taxa belonging to Centaurea, Cyanus, Psephellus and Rhaponticoides in Asteraceae using light microscope and scanning electron microscope (SEM). The exomorphic characteristics studied are shape, size, colour and surface pattern of achene, and hair, length and colour of pappus. The results of the present investigation showed that achene size of the studied taxa is 37 × 14 mm. Pappus length is 114 mm, deciduous for three taxa and inner row is differentiated from the outer, 13 mm long, for 10 taxa. SEM studies showed eight different types of achene surface patterns for the studied taxa: Glebulate, glebulate-ruminate, reticulate, ribbed, ruminate, smooth, smooth-glebulate and undulate. Achene characteristics are useful for both intrageneric and intraspecific classification of the studied taxa. Bangladesh J. Plant Taxon. 22(2): 125-136, 2015 (December)